(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The relationship between socio-economic indicators and life expectancy (LE) of the population in the context of the regions of Kyrgyzstan was studied. Correlation analysis revealed a negative relationship between life expectancy and the number of labor force and employed population in 5 subjects of Kyrgyzstan - in Batken, Jalal-Abad, Issyk-Kul, Naryn and Chui regions, with the exception of Osh region, where a positive relationship was established. A positive relationship has been established between life expectancy and indicators of monetary income and expenditure of the population, as well as the average monthly wage in all regions. A negative relationship was shown between life expectancy and the level of general unemployment in all regions, with the exception of Jalal-Abad and Issyk-Kul regions. A study of the relationship between life expectancy and the level of poverty showed a negative relationship in all regions, with the exception of Chui oblast, where a positive relationship was noted. It has been established that the socio-economic condition is an important determinant of life expectancy for the regions of Kyrgyzstan in the period from 2005 to 2020.